Secukinumab-Associated Crystalline Corneal Deposition. Issue 2 (February 2019) - Power, Barry; Pilson, Qistina; Fulcher, Timothy
Abstract : Purpose: To describe the first reported case of corneal crystalline deposition associated with the monoclonal antibody secukinumab (Cosentyx; Novartis, Basel, Switzerland) and the subsequent follow-up of the case. Methods: Case report. Results: An 18-year-old man was referred for a corneal opinion 1 year after commencing secukinumab monoclonal antibody therapy for ankylosing spondylitis. Crystalline corneal deposits were identified at a routine optometrist appointment. The same optometrist had documented normal anterior segment examination 2 years earlier. On examination, anterior stromal refractile crystals were visible in both corneas extending out to the limbus. The patient's best-corrected distance visual acuity was 20/20 bilaterally, and he was asymptomatic. Family history and systemic workup for other causes of crystal deposition were negative. By a process of elimination of other etiologies, we concluded that the monoclonal antibody secukinumab was responsible for the deposition. At the 1-year point of treatment with secukinumab, the patient remains asymptomatic and is still undergoing therapy. Conclusions: To the best of the authors' knowledge, this is the first report of corneal crystal deposition attributed to secukinumab. The number of monoclonal antibodies in use across multiple medical disciplines is increasing, and corneal specialists may see this presentation more frequently in the future. These drugs provide critical disease-modifying treatment to patients with debilitating systemic pathology. It is important that we understand the natural history of their side effects to allow their full utilization.